2014
DOI: 10.1158/2326-6066.cir-13-0206
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Treatment of Stage III Metastatic Melanoma Patients with L19–IL2 Results in Sustained Clinical and Systemic Immunologic Responses

Abstract: L19-IL2 is a recombinant protein comprising the cytokine IL2 fused to the single-chain monoclonal antibody L19. In previous studies, intralesional injection with IL2 has shown efficacy for the locoregional treatment of cutaneous/subcutaneous metastases in patients with advanced melanoma. The objectives of this study were to investigate whether (i) intralesional delivery of a targeted form of IL2 would yield similar results, with reduction of injection frequency and treatment duration; and (ii) systemic immune … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…L19-IL2 is branded as DARLEUKIN ® for clinical use, and is mainly used to treat melanoma, head and neck cancer, and lymphoma in combination with L19-TNF, dacarbazine or rituximab. Recent phase II clinical evaluation of L19-IL2 in treating melanoma patients showed a promising result in terms of reducing metastasis and extending patient survival 77, 78 . The combined treatment of L19-IL2 and dacarbazine was reasonably tolerated, and all side effects encountered in the study were manageable and reversible.…”
Section: Targeting Fibronectin In Cancer Therapymentioning
confidence: 99%
“…L19-IL2 is branded as DARLEUKIN ® for clinical use, and is mainly used to treat melanoma, head and neck cancer, and lymphoma in combination with L19-TNF, dacarbazine or rituximab. Recent phase II clinical evaluation of L19-IL2 in treating melanoma patients showed a promising result in terms of reducing metastasis and extending patient survival 77, 78 . The combined treatment of L19-IL2 and dacarbazine was reasonably tolerated, and all side effects encountered in the study were manageable and reversible.…”
Section: Targeting Fibronectin In Cancer Therapymentioning
confidence: 99%
“…Twenty-five patients with stage IIIB/IIIC melanoma and cutaneous/subcutaneous injectable metastases were treated i.t. with L19-IL-2, resulting in complete response (CR) in 25 % of patients by modified immunerelated response criteria (irRC) [96] (Table 1).…”
Section: Clinical Trials Of It Immunotherapy With Cytokinesmentioning
confidence: 99%
“…Recently, use of the L19-IL2 immunocytokine for the IIT of melanoma patients has been described [41]. Besides an encouraging rate of CR and PR, the results of this trial showed evidence of systemic immune responses, induced by the intralesional treatment.…”
Section: Intralesional Deliverymentioning
confidence: 70%
“…Besides an encouraging rate of CR and PR, the results of this trial showed evidence of systemic immune responses, induced by the intralesional treatment. Furthermore, the loco-regional control of in-transit/satellite metastases translated into a slower progression to distant metastases and in an improved overall survival [41].…”
Section: Intralesional Deliverymentioning
confidence: 99%